Incidência de infecções em pacientes com artrite reumatoide e espondilartrites em uso de medicamentos biológicos: dados do registro brasileiro de medicamentos biológicos (BiobadaBrasil) - Cecconi, Mariana (2017)
INTRODUCTION: Biologic drugs are very important in the treatment of several rheumatic diseases. Register studies around the world have been conducted to monitor the increased risk of infections in patients on this therapy. OBJECTIVE: The objective of this study was verify the incidence rate of infections in rheumatoid arthritis and spondyloarthritis patients on biologic drugs comparing with controls, using disease-modifying antirheumatic drugs (DMARDs). MATERIAL AND METHODS: Analysis of BIOBADABRASIL data from January 2009 to June 2015. This is a cohort of Brazilian patients with rheumatic diseases exposed to biologic drugs and control group exposed to synthetic DMARDs. RESULTS: 1698 patients (rheumatoid arthritis and spondyloarthritis were included, 7119 patients/year. Serious infectious adverse events (SIAE) were more common among patients using tumor necrosis factor inhibitors (aTNFs), ratio 2.34, p<0.001. Spondyloarthritis group had less SIAE than rheumatoid arthritis group, ratio 0.5, p<0.001. SIAE were more frequent in the respiratory tract in all subgroups. CONCLUSION: Biologic drugs are related to an increased risk of SIAE in BIOBADABRASIL. This increased risk is higher in patients with rheumatoid arthritis than spodyloarthritis patients.